2018
DOI: 10.1080/00498254.2018.1445882
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and brain penetration study of chlorogenic acid in rats

Abstract: 1. The present study is designed to investigate the brain distribution and plasma pharmacokinetics profiles of chlorogenic acid (CGA) after intranasal administration in Charles-Foster rats to evaluate whether the CGA molecules are transported directly via the nose-to-brain path. 2. The CGA is administered intravenously (IV) and intranasally (IN) at the dose of 10 mg/kg. Further, its concentration in the plasma, cerebrospinal fluid (CSF) and the whole brain is analyzed by HPLC-UV method. 3. The study observes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Also, the usage of anti-inflammatory drugs to suppress neuroinflammation to alleviate DA neurodegeneration has been seen in different models of PD ( Choi et al, 2005 ). Researchers have particularly focused to study the antioxidant properties of CGA as it crosses the blood–brain barrier whether in its pure form or as its metabolite ( Ito et al, 2008 ; Chu et al, 2009 ; Kumar et al, 2018 ). Throughout our study, we tried to suggest the novel role of CGA by inhibiting the neuroinflammation by decreasing the production of ROS and release of pro-inflammatory cytokines and suppressing the activation of astrocytes by downregulating the expression of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the usage of anti-inflammatory drugs to suppress neuroinflammation to alleviate DA neurodegeneration has been seen in different models of PD ( Choi et al, 2005 ). Researchers have particularly focused to study the antioxidant properties of CGA as it crosses the blood–brain barrier whether in its pure form or as its metabolite ( Ito et al, 2008 ; Chu et al, 2009 ; Kumar et al, 2018 ). Throughout our study, we tried to suggest the novel role of CGA by inhibiting the neuroinflammation by decreasing the production of ROS and release of pro-inflammatory cytokines and suppressing the activation of astrocytes by downregulating the expression of NF-κB.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, CGA displayed strong DPPH free radical quenching ability with IC50 values less than 45 µg mL −1 . After oral administration of 1.2 g kg −1 CGA to mice or intravenous administration of 10 mg kg −1 CGA to rat, the maximum plasma concentration of CGA reaches 82.6 µg mL or 442.498 µg mL, indicating its high bioavailability . Therefore, it is tempting to speculate that CGA, by inhibiting ROS generation and oxidative stress, protects cell from lipotoxicity under a physiologically achievable concentration.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that NDDs are highly correlated with inflammation and accumulation of oxidative stress‐induced damage (Kim & Lee, 2015). The phenolic compound 5‐CQA is thought to be a strong antioxidant and anti‐inflammatory agent, which can cross the blood–brain barrier (BBB) to act directly and/or indirectly on the central nervous system (Heitman & Ingram, 2017; Kumar, Paliwal, et al., 2019). Some earlier long‐term follow‐up studies indicated that components of decaffeinated coffee (mostly 5‐CQA) lower the risk of NDDs such as ischemic stroke, Alzheimer's disease (AD), and Parkinson's disease (PD) (Larsson et al., 2011; Lopez‐Garcia et al., 2009; Mikami & Yamazawa, 2015; Oboh, Agunloye, Akinyemi, Ademiluyi, & Adefegha, 2013; Teraoka et al., 2012).…”
Section: Beneficial Properties For Healthmentioning
confidence: 99%